Family Status and Work Attitudes: An Investigation in a Professional Services Firm. (28th November 2011) - de, Suzanne; Forret, Monica; Haack, Debra; Jonsen, Karsten
<x xml:space="preserve">Abstract</x> To help employees better balance work and family responsibilities, organizations are increasingly offering a variety of work–family programmes. However, anecdotal reports suggest that employees without spouses or children perceive that they receive fewer organizational benefits and bear greater burdens than their married or parent counterparts. By providing a more 'family‐friendly' work environment, organizations may foster perceptions of inequity in people without families (single adults without dependent children, SAWDCs), possibly resulting in lower job satisfaction and other work‐related outcomes. Using a sample of 454 employees of a professional services firm, we examined attitudinal differences between individuals with and without families. Findings suggest that SAWDCs and non‐SAWDCS differed in terms of age, organizational level, use of flexible work arrangements and firm tenure. However, we found no differences in hours worked, job involvement, job satisfaction or organizational commitment. Interestingly, SAWDCs had more favourable perceptions of the organization's work–family culture than non‐SAWDCs, suggesting that those who do not utilize family‐friendly benefits view them more favourably than those who actually need or use the benefits. In addition to identifying directions for future research, we offer suggestions for organizations, including taking a more universal approach to benefits to the advantage of all employees.